2021
DOI: 10.1021/acs.iecr.0c05755
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Preparation of Cyclohexanone Oxime from Liquid-Phase Catalytic Oxidation of Cyclohexylamine with Molecular Oxygen over Glucose-Modified TiO2 under Solvent-Free Conditions

Abstract: A simple and highly efficient method for manufacturing cyclohexanone oxime from solvent-free liquid-phase aerobic oxidation of cyclohexylamine over a glucose-modified TiO 2 catalyst had been developed under mild reaction conditions. The results indicated that glucose-modified TiO 2 -enriched surface hydroxyl groups as an efficient catalyst played a crucial role in activating cyclohexylamine, and 59.8% conversion and 88.6% selectivity to cyclohexanone oxime were achieved. The characterization results by Brunaue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…To date, few research studies on Ce-Mn composite oxides have been reported in solvent-free liquid-phase selective catalytic aerobic oxidation of toluene. Based on this concept and our previous studies of the oxidation reaction, [32][33][34][35][36] a simple and environmentally friendly approach for selective preparation of BAL and BOL from the liquid-phase aerobic oxidation of toluene in a solvent-free system has been successfully developed employing CeO 2 -MnO x composite oxides as an efficient and cheap catalyst. The obtained results from the catalytic aerobic oxidation process of toluene will be reported in detail in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few research studies on Ce-Mn composite oxides have been reported in solvent-free liquid-phase selective catalytic aerobic oxidation of toluene. Based on this concept and our previous studies of the oxidation reaction, [32][33][34][35][36] a simple and environmentally friendly approach for selective preparation of BAL and BOL from the liquid-phase aerobic oxidation of toluene in a solvent-free system has been successfully developed employing CeO 2 -MnO x composite oxides as an efficient and cheap catalyst. The obtained results from the catalytic aerobic oxidation process of toluene will be reported in detail in the present work.…”
Section: Introductionmentioning
confidence: 99%